Structural and dynamic studies of Pr(11BH4)3. (13th September 2021) - Gigante, Angelina; Payandeh, Seyedhosein; Grinderslev, Jakob B.; Heere, Michael; Embs, Jan Peter; Jensen, Torben R.; Burankova, Tatsiana; Remhof, Arndt; Hagemann, Hans
Abstract: Rare earth borohydrides RE (BH4 )3 are studied in the context of energy storage, luminescence and magnetic applications. We have investigated the structural behavior of praseodymium borohydride Pr ( 11 BH4 )3 containing 11 B isotope because of the previously reported negative thermal expansion. Differential scanning calorimetry (DSC), in-situ variable temperature synchrotron radiation powder X-ray diffraction (SR-PXD) and infrared studies reveal that Pr ( 11 BH4 )3 undergoes to a volume contraction during the phase transition from alpha α-Pr ( 11 BH4 )3 to rhombohedral r-Pr ( 11 BH4 )3 phase upon heating to 493 K. Surprisingly, the phase transition persists upon cooling at room temperature. Vibrational analysis also shows that the stretching frequency of BH4 − anion does not change upon heating which indicates that the B–H bond length remains constant during the structural phase transition from α-Pr ( 11 BH4 )3 to r-Pr ( 11 BH4 )3 phase. Additionally, the energy barrier of reorientation motion of the BH4 − anion in the α-phase was estimated to be ca 23 kJ/mol by quasi-elastic neutron scattering (QENS) and Raman spectroscopy. Graphical abstract: Image 1 Highlights: SR-XRD confirms volume contraction at the α-Pr ( 11 BH4 )3 to r-Pr ( 11 BH4 )3 phase transition. Vibrational spectra confirm that B–H bond length do not change at this phase transition. QENS experiments give the activation energy for BH4 reorientation.